1966
DOI: 10.1002/jez.1401620103
|View full text |Cite
|
Sign up to set email alerts
|

Limb regeneration and nerve fiber number in Rana sylvatica and Xenopus laevis

Abstract: Adult Rana sylvatica does not regrow an amputated forelimb whereas Xenopus laevis does. This difference in regenerative behavior has been analyzed in terms of the number of nerve fibers available at the amputation surface because previous studies have shown that nerve fibers must satisfy a quantitative threshold in order that regeneration occur. Our results show that Xenopus has more fibers per unit area than Rana. However, the value for both is far below that of Triturus and, indeed, even lower than that of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1967
1967
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…'Anuran amphibians can regenerate complete limbs only during the early larval stages, and an insufficient supply of nerves has been put forward as one reason for the decline of the regenerative capacity during larval development and for the inability of postmetamorphic frogs' limbs to regenerate (Singer et al 1957;Rzehak and Singer 1966). However, in a recent work (Filoni and Paglialunga 1990) based on denervation of amputated hindlimbs of J(enopus laevis tadpoles at different stages of development, it has been demonstrated that early limbs can also regenerate after denervation and that nerve-dependence for limb regeneration is established proximo-distally during larval development, as the limb undergoes a process of proximo-distal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…'Anuran amphibians can regenerate complete limbs only during the early larval stages, and an insufficient supply of nerves has been put forward as one reason for the decline of the regenerative capacity during larval development and for the inability of postmetamorphic frogs' limbs to regenerate (Singer et al 1957;Rzehak and Singer 1966). However, in a recent work (Filoni and Paglialunga 1990) based on denervation of amputated hindlimbs of J(enopus laevis tadpoles at different stages of development, it has been demonstrated that early limbs can also regenerate after denervation and that nerve-dependence for limb regeneration is established proximo-distally during larval development, as the limb undergoes a process of proximo-distal differentiation.…”
Section: Introductionmentioning
confidence: 99%
“…Amphibian limb regeneration is normally dependent upon a threshold level of innervation [7,9,12]. The proposed neurotophic factor which stim ulates regeneration has not been identified but is thought to be of high molecular weight [2,6].…”
Section: Introductionmentioning
confidence: 99%